China's fault lines : implications & lessons - Jain, Sandeep (New Delhi G.B. Books, 2018)
China has been on an explosive growth trajectory in the last few decades. It was an underdeveloped third world nation. It has now morphed itself into an established Asian power and an emerging global power. This rise and specially the economic rise has been the focus of intense speculation and debate. There is a perception that China may not be able to sustain the meteoric growth of the past due to its numerous internal challenges. The book has tried to holistically examine the various fault lines of China and their likely impact upon China's future. Possibly some of the fissures have been accentuated due to rapid growth.
Keywords: Strategic aspects of individual places; Politics and government; Economic history; China